Township and village enterprises (TVEs) - Pollard, David J. (Henry Stewart Talks, 2013)
The background to TVE development, Evolution of TVEs, The economic contribution of TVEs, TVE statistics and possible reasons for success, TVE models, Some TVE examples (Cord Fabric, Shangfeng, Golden Cat, Kelon), TVE advantages and disadvantages, Comparison of TVEs with SOEs, TVEs and strategic alliances, Recent trends & the future of TVEs